Splenectomy in patients with undiagnosed splenomegaly. Issue 822 (April 1994) - Cronin, C. C.; Brady, M. P.; Murphy, C.; Kenny, E.; Whelton, M. J.; Hardiman, C.
Abstract : Of splenectomies performed in the Cork Regional Hospital over an 11 year period, ten were undertaken primarily for diagnostic purposes. A definitive histological diagnosis was established in nine patients, seven of whom had lymphoma, two with Hodgkin's disease and five with non-Hodgkin's lymphoma. The weight of the excised spleen in all patients with lymphoma exceeded 1 kg; in all those with a diagnosis other than lymphoma, the spleen weighed less than 1 kg. A majority of patients also had symptomatic improvement from reversal of hypersplenism and from relief of the mechanical pressure effects of an enlarged spleen. Operative mortality was zero. Diagnostic splenectomy is a worthwhile procedure. Most patients will have lymphoma.